Influence of Employee Competency and Work Placement Analysis on Increasing Employee Productivity - Herman Sjahruddin; Jefri Putri Nugraha; Rezky Nurbakti; Yakup Yakup; Imam Jayanto (Quantitative Economics and Management Studies, 2023)
The purpose of this research is to analyze the influence of employee competency and employee placement on increasing employee work productivity at a shrimp processing company in Tuban, East Java. The research design used in this study uses a quantitative associative method. Based on the results of the data analysis that has been carried out in the first hypothesis (H1), which states that employee competence has a positive and significant effect on increasing employee work productivity, the t-count value of 9,995 is greater than the t-table value, which is 1,692, testing the second hypothesis (H2) which states that work placement has a positive and significant effect on increasing employee work productivity, the t value is 11,246 greater than the t table value, which is 1,692, which means that employee competency and employee work placement have a positive and significant effect on increasing employee work productivity, while the value The obtained R-square is 0.804 which states that the employee competence and job placement variables affect the increase in employee work productivity by 80.40% and the remaining 19.60% is influenced by other variables.